Taxonomy of Psychrophilic Strains of Bacillus - Larkin, J. M. (1967)
The morphological and physiological characteristics of 20 isolates of psychrophilic Bacillus were compared with 29 strains representing nine species of mesophilic Bacillus and 2 strains of Sporosarcina ureae to determine the taxonomic position of the psychrophiles. The psychrophiles formed four distinct groups which were sufficiently different from the mesophiles to warrant their designation as new species of Bacillus. The names B. psychrosaccharolyticus, B. insolitus, B. globisporus, and B. psychrophilus are proposed for the new species.